Nickel oxide nanoparticles synthesis using plant extract and evaluation of their antibacterial effects on Streptococcus mutans - Moghadam, Nastaran Chokhachi Zadeh; Jasim, Saade Abdalkareem; Ameen, Fuad; Alotaibi, Dalal H.; Nobre, Marcos A. L. [UNESP]; Sellami, Hanen; Khatami, Mehrdad (Springer Nature, 2022)
Dental decay is known in the world as the most common human infectious disease. Ascending process of dental caries index in the world shows the failure of oral disease prevention. Streptococcus mutans bacteria cause acid damage and tooth decay by producing acid over time. Nanomaterials with suitable functionality, high permeability, extremely large surface area, significant reactivity, unique mechanical features, and non-bacterial resistance can be considered as promising agents for antimicrobial and antiviral applications. In this study, nickel oxide (NiO) nanoparticles with size range from 2 to 16 nm containing Stevia natural sweetener were eco-friendly synthesized via a simple method. Additionally, their various concentrations were evaluated on S. mutans bacteria by applying the broth dilution method. The results demonstrated that these spherical NiO nanoparticles had efficient bacteriostatic activity on this gram-positive coccus. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Bacteriostatic activity; Biosynthesis; Dental caries; NiO nanoparticles; Streptococcus mutans